Community-Based Inquiry from within Indigenous Early Learning Communities of Practice: Introduction to the Special Issue. - Yazzie-Mintz, Tarajean; LeClair-Diaz, Amanda; Yazzie-Mintz, Ethan (American Indian Culture & Research Journal, 2024)
An introduction is presented in which editor discusses various articles within the issue on topics including systems of care and learning in early childhood education; and ways to support Indigenous communities in strengthening learning and education.